Transgressive or just unexpected? Heteroglossic gender performance and informal popular music learning. Issue 3 (1st December 2019) - Bylica, Kelly; Butler, Alison; Wright, Ruth
This article explores the tensions between 'doing gender' and 'doing popular music' within the context of informal popular music learning for one group of girls of age 12–14 in a Southwestern Ontario elementary school. Using the transposition of Bakhtin's concepts of monoglossia and heteroglossia to the performance of gender, the authors explore how members of Group G, an all-girl popular music band, perform heteroglossic gender behaviours, even while maintaining and presenting an outwardly monoglossic performance of gender in other respects. Furthermore, we explore how aspects of the girls' behaviours vacillated between traditional gendered discourses and traditional discourses of popular music. Finally, findings suggest that the girls of Group G may not have been deliberately transgressive in their performances of gender but that they may have produced heteroglossic gender performances as part of a process of exploring their own identities. We conclude by considering the informal popular music classroom as a space that may be conducive or constricting towards the possibilities of heteroglossic gender performances and the need for a broadening of pedagogies of popular music that take into consideration both gender and power as it relates to gender.